PEMUNGUTAN PAJAK ATAS TRANSAKSI PERDAGANGAN MELALUI SISTEM ELEKTRONIK YANG BERKEADILAN - Santosa, Anggoro Budi; Mau, Hedwig Adianto; Khalimi, Khalimi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Trade transactions through electronic systems (PMSE) or E-Commerce have experienced rapid development. Indonesia possesses significant economic potential and a large population, making it a highly promising market for PMSE economic activities. Numerous PMSE business actors, both domestic and international, have entered the e-commerce transaction market. However, many of these PMSE actors have not fulfilled their tax obligations effectively, particularly regarding Income Tax and Value Added Tax (VAT). This situation has resulted in an imbalance and perceived injustice between conventional and digital business actors, as well as between domestic and foreign business entities. This research aims to analyze the tax collection mechanisms on trade transactions through electronic systems in Indonesia and to evaluate the application of the principle of fairness in tax collection for such transactions. This study employs normative legal research with a statutory approach, a conceptual approach, and an analytical approach. The results indicate that the government facilitates PMSE tax collection by issuing several tax regulations based on a self-assessment system, complemented by a strengthened withholding system to optimize tax revenue collection. PMSE tax collection also endeavors to establish fairness for business actors by ensuring equal tax obligations between conventional and digital businesses, as well as imposing taxes on transactions conducted by foreign goods or service providers. On the other hand, there remains a necessity for more comprehensive regulations that thoroughly govern tax collection for trade transactions through electronic systems—whether conducted independently or through third parties—covering Income Tax, Value Added Tax, and international taxation aspects